Bone Regeneration Using a Mixture of Silicon-Substituted Coral HA and β-TCP in a Rat Calvarial Bone Defect Model - Roh, Jiyeon (Materials (Basel), 2016)
The demand of bone graft materials has been increasing. Among various origins of bone graft materials, natural coral composed of up to 99% calcium carbonate was chosen and converted into hydroxyapatite (HA); silicon was then substituted into the HA. Then, the Si-HA was mixed with β-tricalcium phosphate (TCP) in the ratios 100:0 (S100T0), 70:30 (S70T30), 60:40 (S60T40), and 50:50 (S50T50). The materials were implanted for four and eight weeks in a rat calvarial bone defect model (8 mm). The MBCP(TM) (HA:β-TCP = 60:40, Biomatalante, Vigneux de Bretagne, France) was used as a control. After euthanasia, the bone tissue was analyzed by making histological slides. From the results, S60T40 showed the fastest bone regeneration in four weeks (p < 0.05). In addition, S60T40, S50T50, and MBCP(TM) showed significant new bone formation in eight weeks (p < 0.05). In conclusion, Si-HA/TCP showed potential as a bone graft material.